2010
DOI: 10.1097/psy.0b013e3181d75319
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Emotional Hyperarousal as a Premorbid Characteristic of Individuals Vulnerable to Insomnia

Abstract: These data suggest that cognitive-emotional hyperarousal may be a premorbid characteristic of subjects vulnerable to insomnia. It seems that maladaptive coping stress strategies and cognitive-emotional hyperarousal predispose to the development of insomnia and that interventions targeting these characteristics may be important in the prevention and treatment of chronic insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(143 citation statements)
references
References 40 publications
13
130
0
Order By: Relevance
“…These findings reveal important associations between key characteristics of both insomnia and depression (5,6,(21)(22)(23)(24)(25). Although the present study focused on insomnia, the role of restless REM sleep in emotion regulation appears highly relevant to other realms of psychiatry.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These findings reveal important associations between key characteristics of both insomnia and depression (5,6,(21)(22)(23)(24)(25). Although the present study focused on insomnia, the role of restless REM sleep in emotion regulation appears highly relevant to other realms of psychiatry.…”
Section: Discussionmentioning
confidence: 90%
“…resolving of emotional distress and whether hyperarousal, in fact, represents the resulting accumulation of this distress. Of note, hyperarousal is not only present across waking and sleep in people suffering from MDD (21) but is also of key importance in the pathophysiology of primary insomnia (6,(22)(23)(24) and a premorbid characteristic of people vulnerable to insomnia (5,25).…”
Section: Significancementioning
confidence: 99%
“…In addition, the highest associations were with frequent nocturnal awakenings and sleep latency [35]. Recent studies with college students (good sleepers) suggest that cognitive-emotional hyperarousal is a premorbid characteristic of people vulnerable for stress-related insomnia [37,38]. Azevedo et al [37] analyzed both sexes separately and found that female pre-sleep cognitive arousal, predisposition to arousal (arousability), perceived academic stress, and sleep loss due to worries were all associated with sleep disruption related to stress/transient insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Several personality and psychological characteristics are recognized as putative predisposing traits of insomnia, including a ruminative personality, 1 high neuroticism, 2 high depression, 2,3 anxiety introversion, and arousability. 2,4 Another predisposing factor of insomnia, which has gained attention in the literature, is a traitlike vulnerability to stress-related insomnia termed sleep reactivity.…”
Section: Introductionmentioning
confidence: 99%